New parameters for the analysis of statokinezigram vectors - Usachev, Vladimir Ivanovich; Gagey, Pierre-Marie; Elyaev, Viktor Egorovich; Kononov, Anton Fedorovich; Pereyslov, Grigory Anatolyevich (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Based on the analysis of the statokinezigram vectors, new stabilometric parameters have been proposed: the Dynamic Stabilization Factor [DSF] and the Dynamic Stabilization Index [DSI]. They reflect the individual properties of the postural system and the functional state of the human body. DSI is stable in time and does not depend on the duration of the stabilometric recording. The principle and algorithm for calculating these parameters are presented. The possibility of evaluating the effectiveness of osteopathic treatment with its help is shown. Computer stabilometry was carried out on the stabilometric platform “Stabilan” with the software “StabMed” Special Design Bureau “Rhythm”, Taganrog, Russia. The sampling rate was 50 Hz.